Analisis Determinan Konsumsi Energi di 5 Negara Islam: Pendekatan Regresi Panel Data - Nashihuddin Al Amin Pulungan; Suhel Suhel; Sukanto Sukanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of Sukuk, population size, Gross Domestic Product (GDP), and Foreign Direct Investment (FDI) on energy consumption, both individually and simultaneously. The study focuses on five OIC member countries—Indonesia, India, Pakistan, Bangladesh, and Nigeria—covering the period from 2014 to 2024. The analysis employs panel data regression (combining cross-sectional and time-series data) with a total sample of 55 observations. Model specification testing was conducted using the Chow Test, Hausman Test, and Lagrange Multiplier (LM) Test to determine the optimal estimation model, complemented by a series of classical assumption tests covering normality, multicollinearity, autocorrelation, and heteroscedasticity. Based on the panel data model specification results, the Common Effect Model (CEM) was selected as the most appropriate model. Estimation results indicate that, simultaneously, the variables of Sukuk, population, GDP, and FDI do not have a significant effect on energy consumption.